A MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst and its preparation method and application
By modifying the MIL-125-NH2 and constructing the MIL-125-PDI/Znin2S4 heterogeneous structure, the problem of sacrifice the existing photocatalytic hydrogenation system is solved, and the efficient hydrogen production and antibiotics are achieved, and the process is simplified, the process is simplified, and the process is simplified, and the process is simplified, and the process is simplified, and the process is simplified, and the process is simplified, and the craftsmanship is simplified. Cost reduction.
Patent Information
- Application Number
- CN202410606084.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-16
AI Technical Summary
Existing photocatalytic hydrogen production systems require the introduction of expensive and environmentally harmful sacrificing agents, and it is difficult to achieve water decomposition and antibiotic removal at the same time.
Develop a MIL-125-PDI/Znin2S4 heterogeneous optical catalyst, modify the MIL-125-NH2 through the PDI organic group and grow at the surface of its surface. Remove antibiotics at the same time.
The visible light absorption range of the catalyst and the separation and metastasis efficiency of the optical carrier of the catalyst, the efficiency of the hydrogen production and antibiotics is achieved, and the preparation process is simplified and the cost is reduced.
Smart Images

Figure CN118543375B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental functional materials, and in particular to a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] The transition from non-renewable fossil fuels to clean renewable fuels is a necessary way to solve energy supply and environmental problems. Using solar energy to produce hydrogen is a viable strategic solution. Two-thirds of the earth is water, and solar energy is an inexhaustible, clean and renewable natural resource. The amount of sunlight reaching the earth's surface every hour actually exceeds the total global energy consumption each year. However, since the extent to which sunlight reaches the earth varies depending on geographic location, season and time, the effective use of solar energy requires conversion and storage in a cost-effective and environmentally friendly way. The combustion of hydrogen fuel only produces water, without any CO2 and NO x The release of solar energy can be stored, so converting solar energy into high-energy-density, carbon-free, and easily transportable hydrogen energy is an effective strategy.
[0003] The cornerstone of photocatalytic hydrogen production is semiconductor photocatalysts, which can absorb solar photons and generate electron-hole pairs for the redox reaction of water. Since the first discovery of TiO2 producing H2 through photoelectrocatalysis in 1972, various semiconductor photocatalysts have been developed. Metal-organic frameworks (MOFs) have become a hot topic of attention due to their large specific surface area, high porosity, interconnected microporous structure, high content of transition metals, and the possibility of being designed and modified after synthesis. They have been widely used in photocatalytic water splitting, organic matter conversion, carbon dioxide reduction and pollutant degradation. Among the MOFs materials studied, Ti-based MOFs have attracted attention due to the following advantages: ①Ti 4+ The small ionic radius can produce a stronger Ti-O bond; ②Ti 4+ The high coordination number increases the structural diversity of metal-oxygen clusters; ③ Under photoexcitation, Ti 4+ / Ti 3+ The reversible redox transition between the two enables Ti-based MOFs to store charge efficiently. However, pure Ti-MOFs usually do not utilize much visible light, and the generated electron-hole pairs are prone to rapid recombination.
[0004] Although many reports focus on MIL-125-NH2, the overlap of the redox sites of the catalyst in the coupling system under the dual strategy regulation of the introduction of organic ligands and the construction of Z-type heterostructures has not been studied, which may ignore the synergistic promotion mechanism under the dual strategy and the reaction pathway of hydrogen production and synergistic degradation. The migration pathway of electrons in the coupling system, the transformation pathway of organic matter, and the synergistic mechanism under the dual strategy are all scientific problems that are currently lacking in research and need to be solved by us.
[0005] In the current photocatalytic hydrogen production system, in order to achieve efficient conversion of hydrogen energy, it is often necessary to introduce a sacrificial agent, such as methanol, ethanol, triethanolamine, sodium sulfide and sodium sulfite. These reagents are expensive and toxic to the environment, which is not conducive to the further development and application of photocatalytic hydrogen production technology. Although there have been many studies on photocatalytic hydrogen production, there are still great limitations in achieving the removal of antibiotics while photocatalytically decomposing water to produce hydrogen. Therefore, it is urgent to develop a new type of high-efficiency visible light responsive photocatalytic material that can both photocatalytically decompose water to produce hydrogen and remove antibiotics. Summary of the invention
[0006] In view of the above problems, the present invention aims to provide a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst and its preparation method and application, which can remove antibiotics while photocatalytically decomposing water to produce hydrogen.
[0007] The technical solution of the present invention is as follows:
[0008] On the one hand, a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst is provided, wherein the heterojunction photocatalyst is a core-shell structure composed of MIL-125-PDI and ZnIn2S4 in a mass ratio of 1:2 to 5, wherein the core-shell structure has MIL-125-PDI as a substrate and a ZnIn2S4 nanosheet layer on the surface.
[0009] Preferably, the diameter and thickness of the MIL-125-PDI are 1-2 μm and 200-300 nm, respectively.
[0010] On the other hand, a method for preparing a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst is provided, comprising the following steps: dispersing MIL-125-PDI in a glycerol solution to obtain a suspension; adding a ZnIn2S4 precursor to the suspension, stirring and mixing, subjecting the mixture to an oil bath reaction, condensation and reflux treatment, and cooling the mixture to room temperature to obtain a product A; and washing and drying the product A to obtain a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst.
[0011] Preferably, the MIL-125-PDI is prepared by the following steps: MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride are mixed and reacted in an oil bath. After the reaction is completed and cooled to room temperature, ethanol is added and stirred to disperse to obtain product B. The product B is then washed and centrifuged multiple times until the pH is neutral, and then dried to obtain MIL-125-PDI.
[0012] Preferably, the mass ratio of the MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride is 10-60:700:3; the reaction temperature under the oil bath conditions is 120-140°C, and the reaction time is 4-6h; the stirring and dispersion time after adding ethanol is 10-20min, and the product B is washed with deionized water and ethanol multiple times and centrifuged until the pH is neutral.
[0013] Preferably, the MIL-125-NH2 is prepared by the following steps: dissolving 2-aminoterephthalic acid in a mixture of N,N-dimethylformamide and anhydrous methanol to obtain a solution, dropping titanium tetraisopropoxide into the solution and stirring, subjecting the solution to a solvent thermal treatment reaction, cooling to room temperature to obtain a product C, and washing and drying the product C to obtain MIL-125-NH2.
[0014] Preferably, the mass ratio of the 2-aminoterephthalic acid, N,N-dimethylformamide and anhydrous methanol is 1-2:30:6; the amount of the titanium tetraisopropoxide added is 1-2 mL; the stirring time for adding the titanium tetraisopropoxide to the solution A is 0.5-1 h; the solvent thermal treatment reaction temperature is 120-150° C., and the reaction time is 24-72 h; the product C is washed alternately with N,N-dimethylformamide and anhydrous methanol.
[0015] Preferably, the MIL-125-PDI is ultrasonically dispersed in the glycerol solution, the MIL-125-PDI addition amount is 100-300 mg, the concentration of the glycerol solution is 10-50 vol%, and the ultrasonic dispersion time is 0.5-1 h; the ZnIn2S4 precursor includes zinc chloride, indium trichloride tetrahydrate and thioacetamide, and the molar ratio of zinc chloride, indium trichloride tetrahydrate and thioacetamide is 1:2:4-8.
[0016] Preferably, the temperature of the oil bath reaction is 70-90°C, and the reaction time is 1-4h; the product A is washed by centrifugation multiple times with deionized water and ethanol; and the drying temperature is 50-80°C.
[0017] On the other hand, there is also provided an application of the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst described in any one of the above items in the photocatalytic decomposition of water to produce hydrogen and synergistically remove antibiotics.
[0018] The beneficial effects of the present invention are:
[0019] (1) The present invention modifies MIL-125-NH2 by PDI organic groups, effectively broadens the visible light absorption range, and significantly improves the hydrogen production rate; the nanosheet ZnIn2S4 is in situ grown on the surface of MIL-125-PDI to form a core-shell structure, achieving close interface contact, which is beneficial to the efficient separation and transfer of photogenerated carriers, effectively suppresses the coincidence of electron-hole pairs, and enhances the photocatalytic reduction reaction;
[0020] (2) The MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst prepared by the present invention can effectively remove antibiotics in water while producing hydrogen through photocatalysis, and has the ability to synergistically remove pollutants;
[0021] (3) The present invention adopts a three-step method of solvent thermal-oil bath-oil bath to synthesize MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst, which simplifies the preparation process and reduces the cost; in the preparation process, the raw materials are easily available and green and pollution-free, the equipment requirements are low, the heterojunction catalyst can be quickly synthesized, and the reaction conditions are highly controllable;
[0022] (4) The MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst prepared by the present invention has high crystallinity, high yield, and no other impurities are generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1 XDR images of samples prepared in Comparative Examples 1, 2, 6 and Example 2;
[0025] Figure 2 The SEM and TEM images of the samples prepared in Comparative Examples 1, 2, 6 and Example 2 are shown;
[0026] Figure 3 The photocatalytic hydrogen production activity diagram of each embodiment and each comparative example under sacrificial agent conditions;
[0027] Figure 4The photocatalytic hydrogen production activity diagram of the sample prepared in Example 2 under the condition of replacing the sacrificial agent with antibiotics and the XDR diagram of the sample before and after adding the sacrificial agent;
[0028] Figure 5 The graphs are hydrogen production activity of the samples prepared in Example 2 in different antibiotic wastewaters, efficiency graphs for removing antibiotics, and a bar graph of TOC removal rate for tetracycline hydrochloride. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0030] On the one hand, the present invention provides a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst, wherein the heterojunction photocatalyst is a core-shell structure composed of MIL-125-PDI and ZnIn2S4 in a mass ratio of 1:2 to 5, and the core-shell structure has MIL-125-PDI as a substrate and a ZnIn2S4 nanosheet layer on the surface.
[0031] In a specific embodiment, the diameter and thickness of the MIL-125-PDI are 1-2 μm and 200-300 nm, respectively. The ZnIn2S4 is in the form of thin nanosheets.
[0032] On the other hand, a method for preparing a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst is provided, comprising the following steps: dispersing MIL-125-PDI in a glycerol solution to obtain a suspension; adding a ZnIn2S4 precursor to the suspension, stirring and mixing, subjecting the mixture to an oil bath reaction, condensation and reflux treatment, and cooling the mixture to room temperature to obtain a product A; and washing and drying the product A to obtain a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst.
[0033] In a specific embodiment, the MIL-125-PDI is prepared by the following steps: MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride are mixed and reacted in an oil bath. After the reaction is completed and cooled to room temperature, ethanol is added and stirred to obtain product B. The product B is then washed and centrifuged multiple times until the pH is neutral, and then dried to obtain MIL-125-PDI.
[0034] In a specific embodiment, the mass ratio of MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride is 10-60:700:3; the reaction temperature under the oil bath condition is 120-140°C, and the reaction time is 4-6h; the stirring and dispersion time of adding ethanol is 10-20min, and the product B is washed with deionized water and ethanol multiple times and centrifuged until the pH is neutral.
[0035] In the above embodiment, the MIL-125-NH2 is subjected to an amidation reaction with the aminocarboxyl ligand in the 3,4,9,10-perylenetetracarboxylic dianhydride to form MIL-125-PDI. The introduction of the organic ligand PDI significantly improves the light response range of MIL-125-NH2 and the efficiency of photogenerated carrier separation.
[0036] It should be noted that the above embodiment is only a preferred preparation method of MIL-125-PDI. Those skilled in the art may use other preparation methods to prepare the MIL-125-PDI when the structural formula of MIL-125-PDI is known.
[0037] In a specific embodiment, the MIL-125-NH2 is prepared by the following steps: dissolving 2-aminoterephthalic acid in a mixture of N,N-dimethylformamide and anhydrous methanol to obtain a solution, dropping titanium tetraisopropoxide into the solution and stirring, subjecting the solution to a solvent thermal treatment reaction, cooling to room temperature to obtain a product C, washing the product C, and drying to obtain MIL-125-NH2. The room temperature is 20 to 30°C.
[0038] In a specific embodiment, the mass ratio of the 2-aminoterephthalic acid, N,N-dimethylformamide and anhydrous methanol is 1-2:30:6; the amount of the titanium tetraisopropoxide added is 1-2 mL; the stirring time for adding the titanium tetraisopropoxide to the solution A is 0.5-1 h; the solvent thermal treatment reaction temperature is 120-150° C., and the reaction time is 24-72 h; the product C is washed alternately with N,N-dimethylformamide and anhydrous methanol.
[0039] It should be noted that the above embodiment is only a preferred preparation method of MIL-125-NH2. Those skilled in the art may use other preparation methods to prepare the MIL-125-NH2 when the structural formula of MIL-125-NH2 is known.
[0040] In a specific embodiment, the MIL-125-PDI is ultrasonically dispersed in the glycerol solution, the MIL-125-PDI addition amount is 100-300 mg, the concentration of the glycerol solution is 10-50 vol%, and the ultrasonic dispersion time is 0.5-1 h; the ZnIn2S4 precursor includes zinc chloride, indium trichloride tetrahydrate and thioacetamide, and the molar ratio of zinc chloride, indium trichloride tetrahydrate and thioacetamide is 1:2:4-8.
[0041] In a specific embodiment, the temperature of the oil bath reaction is 70-90°C, the reaction time is 1-4h; the product A is centrifuged and washed multiple times with deionized water and ethanol; the drying temperature is 50-80°C
[0042] On the other hand, the present invention also provides an application of the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst described in any one of the above items in the photocatalytic decomposition of water to produce hydrogen and synergistically remove antibiotics.
[0043] Example 1
[0044] A MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst is prepared by the following steps:
[0045] (1) At room temperature (20-30°C), 14 mmol of 2-aminoterephthalic acid was weighed and dissolved in a mixture of 40 mL of N,N-dimethylformamide (DMF) and 10 mL of anhydrous methanol to obtain a solution; then 1.5 mL of titanium tetraisopropoxide was added dropwise to the solution and stirred for 1 hour, and then the solution was transferred to a high-pressure reactor and maintained at 150°C for 72 hours for solvent thermal treatment; after the reaction was completed and cooled to room temperature, the obtained product C was washed alternately with DMF and anhydrous methanol, dried in a vacuum oven at 80°C, and ground to obtain MIL-125-NH2 powder;
[0046] (2) Weigh 250 mg of MIL-125-NH2, 7 g of imidazole and 30 mg of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), mix them thoroughly, transfer them to a round-bottom flask, and react them in an oil bath at 120°C for 6 h; after the reaction is cooled to room temperature, add ethanol and stir to disperse for 20 min, then wash with deionized water and ethanol several times, centrifuge until the pH is neutral, dry in an oven at 80°C, and grind to obtain MIL-125-PDI. 250 powder;
[0047] (3) Weigh 50 mg of MIL-125-PDI 250The powder was ultrasonically dispersed in a 20 vol% glycerol solution to obtain a suspension. Then 2 mmol zinc chloride (ZnCl2), 4 mmol indium trichloride tetrahydrate (InCl3·4H2O) and 8 mmol thioacetamide were weighed and stirred to dissolve in the suspension. The obtained mixture was transferred to a round-bottom flask, and the reaction was condensed and refluxed in an oil bath at 90°C for 4 hours, then cooled to room temperature. The obtained product was washed by centrifugation with deionized water and ethanol several times, dried in an oven at 80°C, and ground to obtain a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst, recorded as 50MIL-125-PDI 250 / ZIS.
[0048] Example 2
[0049] Different from Example 1, the MIL-125-PDI added in step 3 of this example 250 The powder is 100 mg, and the prepared heterojunction photocatalyst is recorded as 100MIL-125-PDI 250 / ZIS.
[0050] Example 3
[0051] Different from Example 1, the MIL-125-PDI added in step 3 of this example 250 The powder is 150 mg, and the prepared heterojunction photocatalyst is recorded as 150MIL-125-PDI 250 / ZIS.
[0052] Example 4
[0053] Different from Example 1, the MIL-125-PDI added in step 3 of this example 250 The powder is 200 mg, and the prepared heterojunction photocatalyst is recorded as 200MIL-125-PDI 250 / ZIS.
[0054] Comparative Example 1
[0055] Different from Example 1, this comparative example only performs the operation of step 1 to prepare MIL-125-NH2.
[0056] Comparative Example 2
[0057] Different from Example 1, this comparative example only carried out steps 1 and 2, and the final product was recorded as MIL-125-PDI 250 .
[0058] Comparative Example 3
[0059] Different from Comparative Example 2, the MIL-125-NH2 weighed in step 2 of this comparative example is 150 mg, and the final product is recorded as MIL-125-PDI 150 .
[0060] Comparative Example 4
[0061] Different from Comparative Example 2, the MIL-125-NH2 weighed in step 2 of this comparative example is 200 mg, and the final product is recorded as MIL-125-PDI 200 .
[0062] Comparative Example 5
[0063] Different from Comparative Example 2, the MIL-125-NH2 weighed in step 2 of this comparative example is 300 mg, and the final product is recorded as MIL-125-PDI 300 .
[0064] Comparative Example 6
[0065] Under room temperature, 2mmol zinc chloride (ZnCl2), 4mmol indium trichloride tetrahydrate (InCl3·4H2O) and 8mmol thioacetamide were weighed and dissolved in a glycerol solution with a concentration of 20vol% by stirring to obtain solution A. The solution A was transferred to a round-bottom flask, reacted in an oil bath at 90°C for 4h, and then naturally cooled to room temperature. The obtained product was washed by centrifugation with deionized water and ethanol several times, and dried in an oven at 80°C. The obtained product was recorded as ZIS.
[0066] Comparative Example 7
[0067] Different from Comparative Example 6, in this comparative example, 2 mmol ZnCl2 and 2 mmol thioacetamide were weighed and stirred to dissolve in a glycerol solution with a concentration of 20 vol% to obtain solution B, and the obtained product was recorded as ZS.
[0068] Comparative Example 8
[0069] Different from Comparative Example 6, in this comparative example, 4 mmol InCl3·4H2O and 6 mmol thioacetamide were weighed and dissolved in a glycerol solution with a concentration of 20 vol% by stirring to obtain solution C. The obtained product was recorded as IS.
[0070] Comparative Example 9
[0071] Different from Example 2, in step 3 of this comparative example, 2 mmol ZnCl2 and 2 mmol thioacetamide were weighed and stirred to dissolve in the suspension to obtain solution D. The obtained product was recorded as 100 MIL-125-PDI. 250 / ZS.
[0072] Comparative Example 10
[0073] Different from Example 2, in step 3 of this comparative example, 4 mmol InCl3·4H2O and 6 mmol thioacetamide were weighed and stirred and dissolved in the suspension to obtain solution E. The obtained product was recorded as 100 MIL-125-PDI. 250 / IS.
[0074] Comparative Example 11
[0075] In this comparative example, the MIL-125-PDI prepared in step 2 of Example 1 was weighed. 250 100 g of powder and 176 mg of ZIS obtained in Comparative Example 6 were ground thoroughly, and the obtained product was recorded as 100MIL-125-PDI 250 &ZIS.
[0076] Experimental Example 1: X-ray diffraction experiment of different samples
[0077] The samples obtained in Comparative Examples 1, 2, 6 and Example 2 of the present invention were subjected to X-ray diffraction test, and the obtained XRD patterns are as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peaks of the original ZnIn2S4 sample at 2θ of 21.4°, 27.6°, 47.4°, 52.7° and 55.8° are respectively attributed to the (006), (102), (110), (116) and (022) crystal planes of the hexagonal ZnIn2S4. 250 The XRD patterns of the two exhibited strong and sharp diffraction peaks with similar shapes, indicating that the crystal framework of MIL-125-NH2 was maintained during the synthesis process. It is worth noting that in the XRD pattern of MIL-125-PDI / ZnIn2S4, the characteristic peak of MIL-125-NH2 appeared at 2θ of 6.8°, confirming the successful composite of MIL-125-PDI and ZnIn2S4.
[0078] Experimental Example 2: Morphological characterization experiment of different samples
[0079] The samples obtained in Comparative Examples 1, 2, 6 and Example 2 of the present invention were studied by scanning electron microscopy and transmission electron microscopy for the detailed morphology and microstructure of the composite materials. The obtained SEM and TEM images are shown in FIG. Figure 2 As shown, Figure 2 a is the SEM image of MIL-125-NH2, Figure 2 b is the TEM image of MIL-125-NH2. Figure 2 c is MIL-125-PDI 250 SEM images of Figure 2 d is MIL-125-PDI 250TEM image of Figure 2 e is the SEM image of ZnIn2S4, Figure 2 f is the TEM image of ZnIn2S4, Figure 2 g is 100MIL-125-PDI 250 / SEM image of ZnIn2S4, Figure 2 h is 100MIL-125-PDI 250 TEM image of / ZnIn2S4. Figure 2 a and Figure 2 As can be seen from (b), MIL-125-NH2 shows a regular and smooth disc-like structure with a diameter and thickness of 1-2 μm and 200-300 nm, respectively. Figure 2 c and Figure 2 d It can be seen that after the MIL-125-PDI is modified with PDI organic groups 250 The shape and size of the MIL-125-NH2 have not changed significantly, but the surface has become rougher. Figure 2 e and Figure 2 As can be seen from f, ZnIn2S4 is a flower ball structure composed of cross-linked nanosheets. Figure 2 g and Figure 2 h can be seen in MIL-125-PDI 250 The in-situ grown ZnIn2S4 forms a compact thin layer of wrinkled structure, completely covering the MIL-125-PDI 250 The surface forms a regular cluster structure. The experimental results show that MIL-125-PDI 250 / ZnIn2S4 composites were successfully prepared, among which MIL-125-PDI 250 The interface between MIL-125-PDI and ZnIn2S4 is in close contact, which promotes the efficient separation and transfer of photocarriers between MIL-125-PDI and ZnIn2S4. In addition, the irregular stacking structure on the surface is conducive to enhancing the absorption of light through diffraction and reflection effects, which has potential benefits for photocatalytic applications.
[0080] Experimental Example 3: Photocatalytic hydrogen production performance experiment of different samples under sacrificial agent conditions
[0081] The performance of the catalyst was tested using the photocatalytic hydrogen production activity evaluation system of Zhongjiao Jinyuan. Triethylamine was used as a sacrificial agent, and the samples obtained in Comparative Examples 1 to 11 and Examples 1 to 4 were used as catalysts in this experiment. 40 mL of acetonitrile, 5 mL of water and 5 mL of triethylamine were accurately measured with a measuring cylinder and mixed as a reaction solution to prepare multiple groups of reaction solutions. Then 10 mg of samples obtained in Comparative Examples 1 to 8 and Examples 1 to 4 were weighed and added to each group of reaction solutions and transferred to different glass reactors. Subsequently, each group of solutions was ultrasonically dispersed for 10 min to mix the above samples evenly. Before the reaction, the reaction system was vacuumed with a vacuum pump for about 30 min to remove dissolved gases in the water. In addition, the reaction temperature was controlled to be maintained at 6 ° C by circulating condensed water to ensure that the moisture content in the gas was at an extremely low level. Adjust the position and height of the simulated light source so that the xenon lamp (300 W) is as close to the solution as possible from top to bottom, turn on the xenon lamp, and adjust the current to 15 mA. The system reacted continuously for 4 hours, and samples were taken every hour. The online GC sampling and detection took 10 minutes. After the GC peak was completed, the system was evacuated to vacuum again. Figure 3 As shown, Figure 3 a and Figure 3 b is MIL-125-NH2, MIL-125-PDI 150 、MIL-125-PDI 200 、MIL-125-PDI 250 and MIL-125-PDI 300 The hydrogen production rate diagram in triethylamine sacrificial agent; Figure 3 c and Figure 3 d is MIL-125-PDI 250 、50MIL-125-PDI 250 / ZnIn2S4,100MIL-125-PDI 250 / ZnIn2S4,150MIL-125-PDI 250 / ZnIn2S4,200MIL-125-PDI 250 / Hydrogen production rate diagram of ZnIn2S4 and ZIS; Figure 3 e and Figure 3 f is the hydrogen production rate diagram of ZS, ZIS and IS; Figure 3 g and Figure 3 h is 100MIL-125-PDI 250 / ZIS, 100MIL-125-PDI 250 / ZS, 100MIL-125-PDI 250 / IS, 100MIL-125-PDI 250 &Hydrogen production rate diagram of ZIS.
[0082] from Figure 3 a and Figure 3 b It can be seen that the hydrogen production rate of MIL-125-NH2 in triethylamine sacrificial agent is 0.13 mmol·g -1 ·h -1 ;MIL-125-PDI 250 The hydrogen production rate is 1.99 mmol·g -1 ·h -1 , which is 7.72 times that of pure MIL-125-NH2, indicating that after MIL-125-NH2 is modified with PDI organic groups, the visible light absorption range is effectively broadened and the hydrogen production rate is significantly improved. Figure 3 c and Figure 3 d It can be seen that single ZnIn2S4 also exhibits limited photocatalytic hydrogen production performance, with a rate of 6.39 mmol·g -1 ·h -1 After being compounded with MIL-125-PDI, the hydrogen production rate is improved to varying degrees. This is because a heterojunction is formed between ZnIn2S4 and MIL-125-PDI. The 100MIL-125-PDI prepared in Example 6 250 The maximum hydrogen production rate of ZnIn2S4 can reach 16.26mmol·g -1 ·h -1 , which is 2.55 times that of ZnIn2S4. This performance improvement is attributed to the fact that MIL-125-PDI / ZnIn2S4 may have a directional electron transfer pathway from the outside to the inside, which can effectively inhibit the recombination of electron-hole pairs and enhance the photocatalytic reduction reaction. In addition, the hydrogen production performance of ZnIn2S4 and different metal sulfides was compared. Figure 3 e and Figure 3 The results show that ZnIn2S4 has better hydrogen production performance than single metal sulfides, and the hydrogen production rate is 6.48 times that of ZnS (ZS) and 20.57 times that of In2S3 (IS). Figure 3 g and Figure 3 h shows that the ZnIn2S4 precursor and 100MIL-125-PDI 250 The composite heterojunction photocatalyst has higher hydrogen production activity than other sulfide-based heterojunction photocatalysts; the synthesized ZnIn2S4 finished product and 100MIL-125-PDI 250 The hydrogen production rate of the product obtained by physical grinding is lower than that of the product using ZnIn2S4 precursor and 100MIL-125-PDI 250 The heterojunction photocatalyst prepared by the composite further shows that ZnIn2S4 and 100MIL-125-PDI 250 The formation of a heterojunction is not a simple physical mixture.
[0083] The experimental results show that the photocatalytic hydrogen production performance of the catalyst is significantly improved by modifying the PDI organic group and constructing the heterojunction between ZnIn2S4 and MIL-125-PDI. In particular, the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst exhibits the highest hydrogen production rate due to its excellent electron transfer ability and the characteristics of inhibiting electron-hole recombination, proving the great potential of this composite material in the field of photocatalytic hydrogen production.
[0084] Experimental Example 4: Photocatalytic cycle experiment of heterojunction photocatalyst under the condition of antibiotics replacing sacrificial agents
[0085] Different antibiotics were used to replace triethylamine in Experimental Example 3 as sacrificial agent, and 100 MIL-125-PDI was prepared in Example 2. 250 / ZIS heterojunction photocatalyst sample was used as the photocatalyst, and other reaction conditions were the same as those in Experiment 3. Before illumination, the residual gas in the reaction system was removed and kept in the dark for 30 minutes to reach adsorption equilibrium. The system reacted continuously for 4 hours, and samples were taken every hour, and GC sampling and detection were performed. At the same time, 2 ml of antibiotic liquid was extracted by membrane filtration, and the system was evacuated to vacuum again. Subsequently, high performance liquid chromatography was used to determine the absorbance of the antibiotic at a fixed wavelength. Figure 4 a is 100MIL-125-PDI prepared in Example 2 250 / ZIS heterojunction photocatalyst sample cyclic hydrogen production activity diagram in antibiotic liquid; Figure 4 b is 100MIL-125-PDI before and after using sacrificial agent 250 / ZnIn2S4 heterojunction photocatalyst X-ray diffraction pattern.
[0086] from Figure 4 a It can be seen that 100MIL-125-PDI 250 The hydrogen production rate of the ZnIn2S4 heterojunction photocatalyst increased from 16.26 mmol·g -1 ·h -1 Down to 15.11mmol·g -1 ·h -1 After the third cycle, the sacrificial agent was added, and the concentration was restored to 17.64 mmol·g in the fourth cycle. -1 ·h -1 The results showed that the long-term experiment may have led to the consumption of the sacrificial agent, thus causing a decrease in the hydrogen production rate of the heterojunction photocatalyst.
[0087] 100MIL-125-PDI before and after using sacrificial agent 250 / ZnIn2S4 heterojunction photocatalyst was subjected to X-ray diffraction. Figure 4 b It can be seen that after using the catalyst, 100MIL-125-PDI 250 There is no obvious change in the crystal structure of the / ZnIn2S4 heterojunction photocatalyst, indicating that it has good stability and recyclability.
[0088] Experimental Example 5: Experiment on the hydrogen production activity of heterojunction photocatalysts in different antibiotics and the efficiency of removing antibiotics
[0089] Tetracycline hydrochloride (TC-HCl), sulfamethoxazole (SMX), ofloxacin (OFL) and amoxicillin (AMX) were selected as target antibiotics to replace the sacrificial agents, and the photocatalytic redox performance of the catalysts was studied. Figure 5 The hydrogen production activity of the sample prepared in Example 2 in different antibiotic wastewaters, the efficiency of removing antibiotics, and the TOC removal rate of tetracycline hydrochloride are shown. Figure 5 a is 100MIL-125-PDI with TC-HCl, SMX, OFL, AMX and H2O added respectively 250 / ZIS hydrogen production rate diagram, Figure 5 b is 100MIL-125-PDI with TC-HCl, SMX, OFL, AMX and H2O added respectively 250 / Antibiotic removal rate diagram of ZIS, Figure 5 c is 100MIL-125-PDI with TC-HCl, SMX, OFL, AMX and H2O added respectively 250 / ZIS hydrogen production rate bar chart, Figure 5 d is 100MIL-125-PDI with TC-HCl, SMX, OFL, AMX and H2O added respectively 250 / Histogram of antibiotic removal rates of ZIS.
[0090] from Figure 5 a and Figure 5 As can be seen from Figure b, compared with pure water, the addition of four antibiotics can significantly increase the photocatalytic hydrogen production rate. Figure 5 c It can be seen that 100MIL-125-PDI 250 The photocatalytic hydrogen production rate and antibiotic removal rate of / ZIS in TC-HCl solution were the highest, 0.51 mmol·g -1 ·h -1 and 1.22h -1 The differences in photoactivity may be related to their chemical structures, physicochemical properties, and the interaction between the catalyst and the antibiotic. Figure 5d It can be seen that after 240 minutes under simulated sunlight irradiation, the mineralization efficiency of TC-HCl by MIL-125-PDI / ZnIn2S4 was 66.62%. The results show that although TC-HCl was completely degraded within 240 minutes, it was not completely mineralized into CO2 and H2O, and there were still many intermediates in the reaction system.
[0091] The experimental results show that using antibiotics instead of sacrificial agents and using solar energy for photocatalytic hydrogen production to synergistically remove antibiotics can not only achieve solar energy conversion and clean energy development at the same time, but also contribute to environmental remediation and the preparation of organic by-products.
[0092] In summary, the present invention significantly broadens the visible light response range and enhances the generation, separation and transmission efficiency of photogenerated carriers through organic ligand grafting and close interface contact between heterojunctions; the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst prepared by the present invention can photocatalytically decompose water to produce hydrogen while removing antibiotics. Compared with the prior art, the present invention has significant progress.
[0093] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst, characterized in that: The heterojunction photocatalyst is a core-shell structure composed of MIL-125-PDI and ZnIn2S4 in a mass ratio of 1:2-5, wherein the core-shell structure has MIL-125-PDI as a substrate and a ZnIn2S4 nanosheet layer on the surface; The heterojunction photocatalyst is prepared by the following steps: MIL-125-PDI is dispersed in a glycerol solution to obtain a suspension; a ZnIn2S4 precursor is added to the suspension, stirred and mixed, subjected to an oil bath reaction, condensed and refluxed, and then cooled to room temperature to obtain a product A, wherein the temperature of the oil bath reaction is 70-90°C and the reaction time is 1-4 h; the product A is washed and dried to obtain a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst.
2. The MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 1, characterized in that: The diameter and thickness of the MIL-125-PDI are 1-2 μm and 200-300 nm, respectively.
3. A method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: MIL-125-PDI is dispersed in a glycerol solution to obtain a suspension; a ZnIn2S4 precursor is added to the suspension, stirred and mixed, subjected to an oil bath reaction, condensed and refluxed, and then cooled to room temperature to obtain a product A, wherein the temperature of the oil bath reaction is 70-90°C and the reaction time is 1-4 h; the product A is washed and dried to obtain a MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst.
4. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 3, characterized in that: The MIL-125-PDI is prepared by the following steps: MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride are mixed and reacted under oil bath conditions, after the reaction is completed and cooled to room temperature, ethanol is added and stirred to disperse to obtain product B, and then the product B is washed and centrifuged multiple times until the pH is neutral, and MIL-125-PDI is obtained after drying.
5. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 4, characterized in that: The mass ratio of MIL-125-NH2, imidazole and 3,4,9,10-perylenetetracarboxylic dianhydride is 10-60:700:3; the reaction temperature under the oil bath condition is 120-140°C, and the reaction time is 4-6 h; the stirring and dispersion time of adding ethanol is 10-20 min, and the product B is washed with deionized water and ethanol for multiple times and centrifuged until the pH is neutral.
6. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 4, characterized in that: The MIL-125-NH2 is prepared by the following steps: dissolving 2-aminoterephthalic acid in a mixture of N,N-dimethylformamide and anhydrous methanol to obtain a solution, dropping titanium tetraisopropoxide into the solution and stirring, subjecting the solution to a solvent thermal treatment reaction, cooling the solution to room temperature to obtain a product C, and washing and drying the product C to obtain MIL-125-NH2.
7. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 6, characterized in that: The mass ratio of the 2-aminoterephthalic acid, N,N-dimethylformamide and anhydrous methanol is 1-2:30:6; the amount of the titanium tetraisopropoxide added is 1-2 mL; the stirring time of adding the titanium tetraisopropoxide to the solution A is 0.5-1 h; the solvent thermal treatment reaction temperature is 120-150 ° C, and the reaction time is 24-72 h; the product C is washed alternately with N,N-dimethylformamide and anhydrous methanol.
8. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to any one of claims 3 to 7, characterized in that: The MIL-125-PDI is ultrasonically dispersed in the glycerol solution, the MIL-125-PDI addition amount is 100~300 mg, the concentration of the glycerol solution is 10~50vol%, and the ultrasonic dispersion time is 0.5~1 h; the ZnIn2S4 precursor includes zinc chloride, indium trichloride tetrahydrate and thioacetamide, and the molar ratio of zinc chloride, indium trichloride tetrahydrate and thioacetamide is 1:2:4~8.
9. The method for preparing the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst according to claim 3, characterized in that: The product A is centrifugally washed multiple times with deionized water and ethanol; the drying temperature is 50-80°C.
10. Use of the MIL-125-PDI / ZnIn2S4 heterojunction photocatalyst as claimed in claim 1 or 2 in photocatalytic decomposition of water to produce hydrogen and synergistically remove antibiotics.
Citation Information
Patent Citations
ZnIn2S4 / NH2-MIL-125(Ti) composite visible-light catalyst and preparation method thereof
CN105964305A
ZnIn2S4 coated CuCo2S4 heterojunction photocatalyst, preparation method and application
CN117258805A
Cited By
ZnIn2S4-coated Bi0. 5Na0. 5TiO3 composite heterojunction photocatalyst as well as preparation method and application thereof
CN121911444A